The Homologous Recombination Repair Pathway is Associated with Resistance to Radiotherapy in Nasopharyngeal Carcinoma - Wang, Zhihai (Int J Biol Sci, 2020)
Radiotherapy plays a major role in the management of nasopharyngeal carcinoma (NPC). However, the radioresistant cells limit its efficiency and drive recurrence inside the irradiated tumor volume leading to poor outcome for patients. To illuminate the signal pathway involved in the radioresistance and evaluate the potential for predicting NPC response to radiotherapy, we established the radioresistant NPC cell line (CNE2-RR) derived from NPC cell line CNE2 by gradually increased the radiation dose (total 60 Gy), and the radioresistance of CNE2-RR cells was evaluated by the colony formation, FCM and comet assays. Furthermore, comparison of established CNE2-RR cell line to parental cell line found the homologous recombination repair (HRR) proteins differences involved in NPC radioresistance. In addition, the differentially expressed proteins were further validated by western blotting, immunofluorescence and IHC in tumor xenografs and radioresistant NPC tissues. Furthermore, the correlation of HRR proteins expression levels with NPC radioresistance were evaluated. The results showed that the upregulation of HRR proteins were significantly correlated with NPC radioresistance. In addition, using the Youden Index cutoff value, a panel of the HRR proteins analyses revealed a sensitivity of 70%, specificity of 72%. Furthermore, silencing NFBD1 enhanced the radiosensitivity of CNE2-RR cells by impairing IR-inducing γ-H2AX and HR proteins foci formation. These results suggest that controlling the HRR signaling pathway may hold promise to overcome NPC radioresistance.